Women’s Vulnerability on Social Media: The Relationship Between Sexism and Self-Esteem - Annisa Karkata; Intan Rahmawati; Sumi Lestari (Journal of Educational, Health and Community Psychology, 2026)
Instead of being a safe space, social media can be a breeding ground for sexism, especially against women. This study aims to examine the relationship between sexism and self-esteem among women who use social media, as well as to explore its dynamics. In line with this objective, the researchers used a mixed method, combining quantitative and qualitative methods used sequentially. The first stage involved a quantitative analysis, utilizing a sample of N = 372 respondents. The results showed a significant negative relationship with a low effect. This indicates that the higher the level of sexism, the lower the self-esteem of female social media users. The second stage was qualitative, using three informants. Based on the results of interviews with the three informants, it was found that two of them had experienced hostile sexism, while one informant tended to have benevolent sexist beliefs. Based on qualitative data collection, it was also found that all three had fluctuating self-esteem, namely, feelings of discomfort experienced by the three informants when receiving sexist comments. However, on the other hand, the three informants also tended to fight back and apply coping strategies.